Patient Protection in the Health Service System Based on Law Number 17 of 2023 Concerning Health - Agung Suhirman; Imam Ropii (Rechtsvinding, 2026)
This study aims to analyze the implementation of patient protection in the health service system based on Law Number 17 of 2023 concerning Health. The method used is a normative method, with a study approach to applicable legal norms through literature studies in the form of books, journals, and the latest official regulatory documents. The analysis was carried out systematically to understand the substance, implications, and effectiveness of the provisions of the law in protecting patients' rights. The results of the study show that Law Number 17 of 2023 provides a strong legal basis in guaranteeing patients' rights to information, approval of medical procedures, and quality health services. However, the implementation of patient protection still faces various obstacles such as a lack of understanding of medical personnel and health facility managers regarding the new rules, limited resources, and a complaint mechanism that is not optimal. The active role of medical personnel and health institutions is crucial in implementing this protection, especially through the application of professional standards, effective communication with patients, and strict supervision. Strategic efforts identified include increasing socialization and education, strengthening accountability, utilizing information technology, developing an organizational culture that respects patients' rights, and strengthening cross-sector cooperation. The implementation of these measures is expected to improve the quality of safe, fair, and sustainable health services, while increasing public trust in the national health system.